2021
DOI: 10.3389/fmed.2021.613419
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health and Its Aetiological Role in Behçet's Disease

Abstract: Behçet's disease (BD) is a chronic multi-systemic inflammatory disorder characterised by oro-genital ulcers, cutaneous manifestations, ocular, vascular, neurologic and gastrointestinal involvement. Complex interactions operating on the genetic background e.g.(HLA51), of infectious and other environmental agents, together with immune dysregulation impacts on the pathogenesis of BD. This suggests that the environmental factors triggering immune responses may activate clinical manifestations in genetically suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“…Studies, including our own, have concluded that the oral health of BD patients is impaired ( 14 , 55 57 ) while clinical treatment of oral symptoms results in better outcomes of systemic disease ( 38 ). Furthermore, the importance of dental and periodontal treatment for controlling oral ulceration activity and systemic disease has been reported ( 54 ) and highlighted in several studies, however its importance in the preventative management of BD has remained largely unrecognised ( 58 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies, including our own, have concluded that the oral health of BD patients is impaired ( 14 , 55 57 ) while clinical treatment of oral symptoms results in better outcomes of systemic disease ( 38 ). Furthermore, the importance of dental and periodontal treatment for controlling oral ulceration activity and systemic disease has been reported ( 54 ) and highlighted in several studies, however its importance in the preventative management of BD has remained largely unrecognised ( 58 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, male gender was identi ed as an independent risk factor for oral health in healthy controls. Immunosuppressive therapy was found to be effective in reducing the number of oral ulcers in severe BD patients compared to those with moderate and milder symptoms, which may help improve oral health (7,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Topical interventions range from oral health promotion to inert barriers to active treatments such as sprays, mouth rinses, locally dissolving tablets, pastes, or gels. Discomfort and pain linked to mucosal lesions may contribute to a poor oral hygiene practice, which in turn induces infective foci, worsening of local inflammation, and dysbiosis, and may contribute to increase systemic disease activity [ 87 ]. Dental plaque accumulation is associated with a more severe disease course [ 88 ].…”
Section: Treatmentmentioning
confidence: 99%